Ochotona hyperborea subsp. hyperborea - Lissovsky, Andrey A.; Obolenskaya, Ekaterina V.; Dokuchaev, Nikolai E.; Okhlopkov, Innokentiy M. (Zenodo, 2021)
Ochotona hyperborea hyperborea (Pallas, 1811) Lagomys hyperboreus var. ferruginea Schrenk, 1858 Lagomys hyperboreus var. normalis Schrenk, 1858 Lagomys litoralis Peters, 1882 Ochotona kolymensis Allen, 1903 Ochotona hyperborea minima Sokolov et al., 1994 Ochotona hyperborea shamani Sokolov et al., 1994 Type.— Specimen unknown; the nominal taxon Lepus hyperboreus was described by P. S. Pallas on the basis of specimens collected by Carl Heinrich Merck (Pallas 1811:152). Type locality.— Chukchi Peninsula “terris Tschuktschicis” (Pallas 1811:152). This toponym can describe large territory; however, C. Merck only visited the northern part of Chukchi Peninsula along the trek from St. Laurent Bay–Mechigmen Bay (13–26 of September 1791)–Kolyutchin Bay (14 October)– Amguema River (18 November)–Chaun River (19 January 1792)–Anyuyskiy Ostrog at the estuary of Angarka River (14 February; 66.85°N, 164.25°E; Merck 1782–1792 [1980]). The detailed map of the route was published by Sarychev (1811). Merck mentioned Anyuyskiy Ostrog as the final point of expedition, hence probably did not collect during the journey to Yakutsk through Nizhnekolymskiy Ostrog. Thus, the route from St. Laurent Bay to Anyuyskiy Ostrog should be considered as the type locality of O. h. hyperborea . Description.— Pikas of the A genetic lineage; northern acoustic race. Besides genetics, this subspecies can be distinguished from neighboring O. h. uralensis by the shape of parietal suture of the skull (Fig. 5). There are differences in the shape of the frequency modulation curve of alarm call with another spatial neighbor— O. h. cinereoflava (Fig. 6). Distribution.— The most northeastern part of the distribution range of the species: Chukchi and Kamchatka Peninsulas, Kolyma and Koryak Uplands, and Indigirka River basin. Provisionally, the distributional border with O. h. uralensis corresponds roughly to the watershed between the Yana and Indigirka River basins (at least its eastern part). Junction with distribution of O. h. cinereoflava is possible to the ...